(untitled) (Research, Society and Development, 2025)
The Transmissible Venereal Tumor (TVT) is a contagious neoplasm affecting dogs, primarily transmitted through sexual contact, but also by licking, sniffing, or biting. This study aims to report a clinical case of a mixed-breed female dog, rescued from abandonment, diagnosed with vulvar TVT. The patient exhibited clinical signs consistent with the neoplasm, confirmed via cytological examination, which revealed round cells with cytoplasmic vacuoles and prominent nuclei. Treatment consisted of chemotherapy with vincristine, resulting in complete remission of lesions after four applications. This case highlights the effectiveness of cytological diagnosis and chemotherapy, as well as the importance of population control.